Protocol for a systematic review of guidelines for rigour in the design, conduct and analysis of biomedical experiments involving laboratory animals. Issue 1 (7th September 2018) - Vollert, Jan; Schenker, Esther; Macleod, Malcolm; Bespalov, Anton; Wuerbel, Hanno; Michel, Martin Christian; Dirnagl, Ulrich; Potschka, Heidrun; Wever, Kimberley E; Steckler, Thomas; Altevogt, Bruce; Rice, Andrew S C
Abstract : Objective: Within the last years, there has been growing awareness of the negative repercussions of unstandardized planning, conduct and reporting of preclinical and biomedical research. Several initiatives have set the aim of increasing validity and reliability in reporting of studies and publications, and publishers have formed similar groups. Additionally, several groups of experts across the biomedical spectrum have published experience and opinion-based guidelines and guidance on potential standardized reporting. While all these guidelines cover reporting of experiments, an important step prior to this should be rigours planning and conduction of studies. The aim of this systematic review is to identify and harmonize existing experimental design, conduct and analysis guidelines relating to internal validity and reproducibility of preclinical animal research. The review will also identify literature describing risks of bias pertaining to the design, conduct and analysis of preclinical biomedical research. Search strategy: PubMed, Embase and Web of Science will be searched systematically to identify guidelines published in English language in peer-reviewed journals before January 2018 (box 1). All articles or systematic reviews in English language that describe or review guidelines on the internal validity and reproducibility of animal studies will be included. Google search for guidelines published on the websites of major funders and professional organisations can be found in (Box 2). Screening and annotation: Unique references will be screened in two phases: screening for eligibility based on title and abstract, followed by screening for definitive inclusion based on full text. Screening will be performed in SyRF (http://syrf.org.uk ). Each reference will be randomly presented to two independent reviewers. Disagreements between reviewers will be resolved by additional screening of the reference by a third, senior researcher. Data management and reporting: All data, including extracted text and guidelines, will be stored in the SyRF platform. Elements of the included guidelines will be identified using a standardized extraction form. Reporting will follow the PRISMA guidelines as far as applicable.